High-performance inkjet printed carbon nanotube thin film transistors with high-k HfO2 dielectric on plastic substrate - Lee, Chun Wei (2013)
Inkjet printing is used to fabricate CN-TFT devices on PET substrate with 70 nm HfO2 gate dielectric. By varying the amount of printing, effective mobility can be raised to 43 cm2 V−1 s−1 with on/off ratio ≥ 104 for devices with channel length 160 μm. This demonstrates that inkjet printing is promising for fabrication of high-performance devices in flexible electronics.